2.6 “Feeding bodies, nurturing identities”. The significance of food for the well-being of Peruvian migrants in Chile - Núñez, Lorena C. (AM. Rivista della Società Italiana di Antropologia Medica, 2004)
2.6 “Feeding bodies, nurturing identities”. The significance of food for the well-being of Peruvian migrants in Chile